"Athlete suspended for presence of banned substance": A storied approach to protecting student-athletes from doping in sport. Issue 3 (2nd September 2019) - Erickson, Kelsey
ABSTRACT: Banned substance use is a growing issue among student-athlete populations but limited research has addressed this concern. The aim of this research was therefore to explore the lived experience of a sanctioned student-athlete in order to expose the contexts and experiences surrounding their sanction and illuminate student-athlete specific doping risk factors. A narrative approach was adopted and one male student-athlete ("Tyler") serving a doping sanction was interviewed. Data is presented in the form of a creative non-fiction story. The story demonstrates the interplay between multiple risk factors that ultimately combined and led to Tyler's doping sanction. Injury and supplementation emerged as particularly significant, as did Tyler's family life. Informed by the story presented, practical implications are offered for supporting student-athletes in avoiding banned substance use. It is hoped that the story will trigger a critical conversation and collective effort towards proactively protecting student-athletes from their doping susceptibility.